Quality of life in animals as a new outcome for surgical research: G-CSF as a quality of life improving factor - Bauhofer, Artur; Witte, Klaus; Lemmer, Björn; Middeke, Martin; Lorenz, Wilfried; Celik, Ilhan (European surgical research, 2002)
Sepsis is still a major problem in human medicine with a high mortality rate. Nearly all attempts to improve the outcome of septic patients with immune modulators failed. In most of these trials only mechanistic endpoints such as mortality rate, complication rate, cytokine levels and physiological parameters were assessed. Only in a very few trials quality of life had been chosen as primary endpoint. In basic research and especially in animal experiments in the field of sepsis and oncology, only molecular investigations which explain drug and treatment interactions were in the focus of the scientific community. Animal models simulating clinical complexity and investigating outcomes like quality of life were very rare. The aim of this study was to demonstrate alterations in sickness behaviour - the animal equivalent to quality of life in man - in rats as a response to sepsis after prophylaxis with G-CSF and antibiotics. Sickness behaviour was assessed by measurement of core body temperature, food and water intake, locomotor activity and circadian rhythm of these parameters. Complex animal experiments in rats were performed including anaesthesia, antibiotic and cytokine (G-CSF) prophylaxis, volume substitution, laparotomy, contamination and infection with human faecal suspension and postoperative analgesia. In group A (sham) and D (antibiotic + G-CSF) the mortality rate was 0% , but in group B (no prophylaxis) 33% (3/9) and in group C (antibiotic prophylaxis) 11% (1/9) of the animals died. Before infection all rats showed clear circadian patterns of locomotor activity and body temperature with physiologically higher values during the night-time. Immediately after operation and infection temperature increased, water and food intake, locomotor activity decreased and circadian rhythms were lost. Body temperature and water consumption were already normalised at day 2 after infection in all groups. Normal food intake was re-established in group C and D at day 3 while one more day was needed for recovery in Group C. Restoration of locomotor activity occurred in group D at day 5, in group C at day 7. In group B locomotor activity remained suppressed during the whole observation period of 8 days postoperatively. In conclusion, in septic rats sickness behaviour, an equivalent to quality of life in humans, is improved rapidly by a prophylaxis with G-CSF in combination with antibiotics and can be used as a new outcome in preclinical surgical research.
Gesehen am 07.04.2022